Položaj Slovencev na Madžarskem po letu 1990 - Munda Hirnök, Katalin (Traditiones (Ljubljana), 2000)
Slovenes living in the Porabje region of Hungary, representing the smallest community of Slovenes living outside Slovenia, had been deprived of ties with their parent nation for decades. In the 1990s they were finaly able to open the Slovene Culture and Information Center - Slovene Hime in Szentgotthard (Monošter)
Keywords: kulturna zgodovina; Slovenci; Slovenes; Madžarska; Hungary